Case report discussion of management of pink tetralogy of Fallot in VACTERL association - Bayushi Eka Putra; Toto Wisnu Hendrarto (Indonesian Pediatric Society, 2019)
Tetralogy of Fallot (TOF) and VACTERL are considered rare entities requiring medical attention with regards to diagnosis and management. When TOF is associated with VACTERL association, case management might differ from a simple case of TOF. Tetralogy of Fallot (TOF) is defined as a complex congenital cardiac abnormality characterized by ventricular septal defect, right outflow tract obstruction, right ventricular hypertrophy, and overriding aorta.1 The term was coined in 1888 by Fallot of Marseilles, even though the defect had been described in 1673 by Steno of Denmark. The entity was then studied extensively to deliver better care management through medical and surgical approaches.2